The effect of dietary n-3 series fatty acids on the number of pleopadal egg and stage 1 juvenile in freshwater crayfish, Astacus leptodactylus Eschscholtz - Harlioglu, Muzaffer Mustafa; Cakmak, Mehmet Nuri; Koprucu, Kenan; Aksu, Onder; Harlioglu, Ayse Gul; Yonar, Serpil Mise; Gundogdu, Hande (Wiley, 2013)
The effect of dietary n-3 series fatty acids on the number of pleopadal egg and stage 1 juvenile in freshwater crayfish, Astacus leptodactylus was investigated. Crayfish were fed with n-3 series fatty acids supplemented diets and a control diet for 251days. Control diet did not comprise additional n-3 series fatty acids. However, D2, D3 and D4 groups were supplemented with n-3 series fatty acids at 1%, 2% and 3% level respectively. Results showed the beneficial effects of dietary n-3 series fatty acids on the production of pleopodal egg and stage 1 juvenile number. At the end of the experiment, pleopodal egg (from 177 to 234) and stage 1 juvenile number (from 167 to 225) increased significantly with increased dietary n-3 series fatty acid level. In addition, an increase in dietary n-3 series fatty acids led to an increase in number of pleopodal egg and stage 1 juvenile produced per gram of female crayfish weight. It can be concluded that the reproductive efficiency of A. leptodactylus (i.e., pleopodal egg and stage 1 juvenile number) can be improved in controlled hatchery conditions by adding n-3 series fatty acid into the diet of this species.
Keywords: Astacus; crayfish; juvenile; n-3 series fatty acid; pleopadal egg